Effect of phosphorus supplementation on the reproductive performance of beef cows grazing Brachiaria humidicola - S'Thiago, Luiz Roberto Lopes; Moraes, Sheila da Silva; Nicodemo, Maria Luiza Franceschi; Rosa, Ivan Valadão; Broring, Nilson (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this experiment was to observe and quantify the effect of two mineral mixtures, as free-choice feeding, one without (M) and other with phosphorus supplement (MP), on the productive and reproductive performance of Nellore beef cows grazing Brachiaria humidicola. This work was conducted at the Fazenda Modelo (Embrapa-Centro Nacional de Pesquisa de Gado de Corte), located in Terenos, MS, Brazil, in two phases, 1st from 1988/92 and 2nd from 1992/94. During the 2nd phase, stocking rate, for the dry period, and suckling days were reduced (from 1.0 to 0.5 cows/ha and 210 to 90 days, respectively). Mineral intake (M = 76 and MP = 112 g/had/day), forage phosphorus level (wet season = 0.16%; dry season = 0.11%), liveweight (1st phase: M = 363±3.3 and MP = 371±3.8 kg; 2nd phase: M = 407±5.7 and MP = 417±6.5 kg), birth percentage (1st phase: M = 67±3.3 and MP = 66±3.5; 2nd phase: M = 75±6.3 and MP = 80±5.7) and weaning of calves (1st phase: M = 86±5.0 and MP = 91±5.3; 2nd phase: M = 55±6.4 and MP = 67±5.7) were measured. Beef cattle is not responsive to P supplementation.
Keywords: breeding; nutrition; minerals; Nellore; tropical grass; reproduction; Brazilian savannas